Funding Decision, Dividend Policy, and Company Growth on Company Value of Primary Goods Sector - Saputri, Saputri; Suripto, Suripto (Interdisciplinary Social Studies, 2022)
Background: The phenomenon that occurs on the Indonesia Stock Exchange shows that the value of the company's value of the company projected through the value of the stock market has decreased even though there is no financial policy carried out by the company. Values change more due to other information such as social and political situations. Aim: This study aims to determine the effect of Funding Decisions, Dividend Policy, and Company Growth on the Value of Companies listed on the Indonesia Stock Exchange from (2015 to 2020). Method: The type of research used is quantitative associative. The sample selection was based on the purposive sampling method, so the samples obtained were 11 companies with 66 observational data. The data analysis technique used is panel data regression analysis, with data processing using the Eviews 9.0 for the Windows program. Findings: The results showed that simultaneously the variables of Funding Decisions, Dividend Policy, and Company Growth had an effect on Firm Value. While partially, the variable of Funding Decision has an effect on firm value, while the variable of dividend policy and firm growth has no effect on firm value.